Preparation method and application of ceramic cutter head material of ceramic tile cutter

Through vacuum sintering and high-energy ball milling, combined with graphite powder, tungsten, cobalt and other elements, a high-strength, toughness and wear resistance silicon nitride ceramic material was prepared, which solved the problem of insufficient hardness and wear resistance of existing ceramic tile cutter materials. The problem has achieved efficient industrial production and use.

CN119118682AActive Publication Date: 2024-12-13吉林工程职业学院
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411270834.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

The existing ceramic tile cutter materials have shortcomings in terms of hardness and wear resistance, especially the hardness and wear resistance of cemented carbides, which leads to a short service life and poor toughness of silicon nitride ceramic materials, which increases processing risks. .

Method used

Using vacuum sintering technology and high-energy ball milling method, combined with graphite powder, tungsten, cobalt and other elements, high-temperature and high-pressure sintering and cerite composite cavity, high-strength, toughness and wear resistance silicon nitride ceramic materials are prepared to form WC-Co The cemented carbide phase and the Co-C solid solution alloy phase enhance the density and toughness of the matrix and prevent oxidation through a vacuum environment.

Benefits of technology

It realizes high toughness and wear resistance of silicon nitride ceramic materials, improves the service life and processing efficiency of the cutter, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118682A_ABST
    Figure CN119118682A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a ceramic cutter head material of a ceramic tile cutter, silicon nitride powder, a sintering aid and a binder are selected as raw materials and mixed, vacuum high-energy ball milling is performed for full wet mixing, and drying is performed in a vacuum drying oven to obtain a carbon-free mixed raw material; pre-pressing and molding the carbon-free mixed raw material, loading a cylindrical blank into a cavity of a vacuum tube furnace, and carrying out high-temperature treatment on the blank in a vacuum environment by adopting a vacuum sintering technology; crushing the carbon-free green body subjected to high-temperature treatment, adding a small amount of graphite powder, carrying out vacuum low-speed ball milling and full mixing to obtain a carbon-containing mixed raw material, and carrying out pre-pressing molding to obtain a carbon-containing green body; and loading the carbon-containing green body into a graphite heating cavity, assembling a pyrophyllite composite block, and sintering the pyrophyllite composite block at high temperature and high pressure by using a diamond hydraulic press to complete the preparation of the beta-Si3N4 sintered body. The beta-Si3N4 sintered body which is high in strength and good in toughness and wear resistance is prepared through the method, operability is high, and the method is suitable for industrial large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of manufacturing cutting tool materials for building materials such as tiles and glass, and specifically relates to a preparation method and application of a silicon nitride ceramic material with high strength, high toughness and strong wear resistance. Background Art

[0002] Tile cutters are one of the commonly used tools for processing important building materials such as tiles and glass. The quality of the cutter head determines the processing quality of the material. At present, the cutter head materials are mainly natural diamond, artificial diamond and cemented carbide. Natural diamond and artificial diamond have super high hardness and strength, but natural diamond is expensive. Although artificial diamond greatly reduces the cost, the synthesis conditions are high, the synthesis temperature and pressure range are narrow, and the diamond cutter has strict requirements on the operator; cemented carbide has good toughness relative to diamond, but its hardness and wear resistance are poor. As a cutter, it is easy to wear, has a short service life, and has a limited range of cutting materials. Therefore, choosing the right tile cutter head material is crucial for the processing of building materials.

[0003] Silicon Nitride (Si 3 N 4 ) Ceramic materials have attracted extensive attention due to their excellent performance in high hardness, high strength, corrosion resistance and good wear resistance. Their hardness and strength are second only to diamond and cubic boron nitride superhard materials, much higher than tiles and glass, and they are abundant in reserves, not limited by resources, and have a wide range of synthesis conditions. For example, as a cutting tool material, it can further reduce production costs. However, its toughness is relatively poor compared to cemented carbide, which increases the probability of uneven force or impact damage during tool head processing. Therefore, ensuring the basic properties of silicon nitride while improving the toughness of the matrix has become an important development direction. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method and application of a ceramic blade head material for a tile cutter. The method has strong operability, and the silicon nitride ceramic has high strength, toughness and wear resistance.

[0005] The technical solution of the present invention:

[0006] A method for preparing a ceramic blade head material for a tile cutter, the method comprising the following steps:

[0007] ①. Select α-Si 3 N 4 Powder, sintering aid powder and binder powder are used as raw materials;

[0008] ②, the mixed powder raw materials selected in ① above are mixed in a certain proportion, and after being fully wet-mixed by vacuum high-energy ball milling for 1-10 hours, they are dried in a vacuum drying oven to obtain a carbon-free mixed raw material;

[0009] ③. Pre-press the carbon-free mixed raw material obtained in ②, load the cylindrical green body into a vacuum tube furnace cavity, and use vacuum sintering technology to perform high-temperature treatment on the green body in a vacuum environment;

[0010] ④. Crush the carbon-free green body obtained after high-temperature treatment in ③, add a small amount of graphite powder, and fully mix by vacuum low-speed ball milling to obtain a carbon-containing mixed raw material, and pre-press and shape to obtain a carbon-containing green body;

[0011] ⑤. Load the carbon-containing blank in ④ into the graphite heating chamber, assemble the pyrophyllite composite block, and sinter it under high temperature and high pressure using a diamond hydraulic press to complete the β-Si 3 N 4 Preparation of sintered bodies.

[0012] Beneficial effects of the present invention:

[0013] 1. The present invention uses W and Co powders as binders and adds a small amount of graphite powder to form a WC-Co cemented carbide phase, thereby enhancing the toughness of the matrix; Co can "consume" the excess C in the matrix, and C enters the Co lattice to form a Co-C solid solution alloy phase, thereby effectively avoiding the remaining C from affecting the matrix performance and enhancing the matrix toughness.

[0014] 2. The present invention adopts high-energy ball milling technology to crush and refine the raw material particles while fully mixing the raw materials, which can enhance the density, toughness and wear resistance of the matrix to a certain extent, while increasing the defect degree of material particles and reducing the reaction activation energy.

[0015] 3. The present invention uses a corundum tube as a container to 3 N 4 The blank is vacuum treated at high temperature. 3 N 4 Under the capillary action of the gaps between the W particles, the molten Co and Ni are fully infiltrated in the blank, which can effectively promote the uniformity of the matrix composition and reduce defects such as "agglomeration" and "bridging" introduced in the powder mixing process; the vacuum (negative pressure) environment can remove the air between the particles of each component, effectively prevent material oxidation, and is more conducive to the infiltration of molten metal into the surrounding area.

[0016] 4. The present invention uses the pyrophyllite composite cavity as a high-pressure reaction vessel to prepare a high-toughness silicon nitride ceramic sintered body under the drive of high temperature and high pressure. The method has strong operability and is suitable for large-scale industrial production.

[0017] 5. The silicon nitride ceramic material prepared by the present invention has a Vickers hardness of more than 20 GPa, high toughness and high density, and a yield rate of more than 95%. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0019] Figure 1 It is a cross-sectional view of the assembly of the pyrophyllite composite block cavity in the process of the present invention.

[0020] Reference numerals:

[0021] Carbon-containing raw material block 1; small graphite sheet 2; plug 3; graphite tube 4; large graphite sheet 5; copper sheet 6; conductive steel cap 7; pyrophyllite composite block 8. DETAILED DESCRIPTION

[0022] In order to solve the problems in the background technology, a method for preparing ceramic blade head materials for tile cutters of the present application is specially invented. The present invention adopts vacuum sintering technology, uses a corundum tube as a reaction container, fully infiltrates the molten metal in the blank under vacuum conditions, and then adopts high temperature and high pressure sintering technology to crystallize silicon nitride under high pressure drive to prepare silicon nitride ceramic materials with high strength, toughness and wear resistance. It is a method that can achieve high efficiency, mass production and industrial application.

[0023] The specific steps of the preparation method of the present invention are:

[0024] α-Si 3 N 4 Micro powder (99.9%, particle size is nanometer and micrometer) is the hard phase matrix, with ZrO 2 (99.9%, particle size is nanometer, micrometer) as sintering aid, and W, Co, Cr, Ni, Ti, etc. (99.9%, particle size is nanometer, micrometer) as binder, binder is W, Co, binder can also include Cr or Ni or Ti, α-Si 3 N 4, the mass ratio of sintering aid and binder is 7:X:3-X (X=0.05-0.5), the mass ratio of binder W and Co is 30:0.5-2, and the mass ratio of Co and other elements in the binder is 1:0-2. The ingredients are mixed according to a certain ratio, and after being fully wet-mixed by vacuum high-energy ball milling for 1-10 hours, they are dried in a vacuum drying oven to obtain a carbon-free mixed raw material. The carbon-free mixed raw material is loaded into a mold, pre-pressed at a pressure of 5-20MPa using a four-column press, and the cylindrical carbon-free blank is loaded into a vacuum tube furnace cavity, and the blank is subjected to high-temperature treatment (1500-1700℃) for 10-30min in a vacuum environment. The carbon-free green body after high temperature treatment is crushed, a small amount of graphite powder is added, and the mixture is fully mixed by vacuum low-speed ball milling for 1-5h to obtain a carbon-containing mixed raw material, which is pre-pressed to obtain a carbon-containing green body. The carbon-containing green body is loaded into a graphite heating cavity, and a pyrophyllite composite block is assembled. The β-Si with high strength, good toughness and wear resistance is prepared by a diamond hydraulic press at high temperature and high pressure (4.0-5.5GPa, 1250-1600℃). 3 N 4 Sintered body.

[0025] Since the method for preparing silicon nitride ceramics of the present invention adopts high-energy ball milling technology, the raw materials can be fully mixed and the particles can be refined, the density of the matrix can be enhanced, the defect degree of the material particles can be increased, and the activation energy of the reaction can be reduced; 3 N 4 The green body is subjected to vacuum high-temperature heat treatment, and the molten metal fully infiltrates between the green body particles, which can effectively promote the uniformity of the matrix composition. The vacuum (negative pressure) environment can remove the air between the particles of each component, which can effectively prevent the material from oxidizing. The silicon nitride ceramic sintered body is prepared under the drive of high temperature and high pressure. The method has strong operability, and the prepared silicon nitride has uniform texture, high strength, good toughness and wear resistance, and is suitable for large-scale industrial production.

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] As attached Figure 1 As shown: Select α-Si with a particle size of 3-5μm and a mass of 5g 3 N 4 , Sintering aid ZrO 2 and binder W, Co mixed powder as the initial raw material (α-Si 3 N4 , sintering aid and binder mass ratio is 7:0.5:2.5 (W:Co=30:1.5)). After fully wet mixing by vacuum high-energy ball milling for 5h, the mixed raw material is dried at 70℃ in a vacuum drying oven. The cylindrical green body is pre-pressed at a pressure of 10MPa using a four-column press, and the cylindrical green body is loaded into a vacuum tube furnace cavity. The green body is subjected to high temperature treatment at 1500℃ for 30min under vacuum. The carbon-free green body after high temperature treatment is crushed, 0.07g of graphite powder is added, and after fully mixing by vacuum low-speed ball milling for 2h, it is pre-pressed at 10MPa, and the carbon-containing raw material green body 1, small graphite flakes 2 and plugs 3 are loaded into the graphite tube 4. Three carbon-containing raw material green bodies 1 and four small graphite flakes 2 are arranged alternately in sequence. The inner diameter of the graphite tube 4 is 17mm and the height is 16mm. Then put the graphite cavity and components 5-7 into the pyrophyllite composite block 8. The size of the pyrophyllite composite block 8 is 32.5mm×32.5mm×32.5mm. The diameter of the synthetic cavity is 18mm. The silicon nitride is sintered at high temperature and high pressure on a diamond hydraulic press. The sintering conditions are 5.5GPa, 1550℃, and the sintering holding time is 30min. After slowly cooling to room temperature, three pieces of Φ14mm×2mm silicon nitride ceramic sheet sintered body materials are obtained after pressure relief. The hardness of the sintered body material is measured to be 23GPa, and the fracture toughness is 13.5MPa·m 1 / 2 .

[0029] Example 2

[0030] As attached Figure 1 As shown: Select α-Si with a particle size of 10-15μm and a mass of 5g 3 N 4 , Sintering aid ZrO 2 and binder W, Co mixed powder as the initial raw material (α-Si 3 N 4, the mass ratio of sintering aid and binder is 7:0.3:2.7 (W:Co=30:1)). After being fully wet-mixed by vacuum high-energy ball milling for 2h, the mixed raw material is dried at 70℃ in a vacuum drying oven. The cylindrical green body is pre-pressed at a pressure of 5MPa using a four-column press, and the cylindrical green body is loaded into a vacuum tube furnace cavity. The green body is subjected to high-temperature treatment at 1600℃ for 30min in a vacuum environment. The carbon-free green body after high-temperature treatment is crushed, 0.08g of graphite powder is added, and after being fully mixed by vacuum low-speed ball milling for 2h, it is pre-pressed at 10MPa, and the carbon-containing raw material green body 1, small graphite flakes 2 and plugs 3 are loaded into the graphite tube 4. Three carbon-containing raw material green bodies 1 and four small graphite flakes 2 are arranged alternately in sequence. The inner diameter of the graphite tube 4 is 17mm and the height is 16mm. Then put the graphite cavity and components 5-7 into the pyrophyllite composite block 8. The size of the pyrophyllite composite block 8 is 32.5mm×32.5mm×32.5mm. The diameter of the synthetic cavity is 18mm. The silicon nitride is sintered at high temperature and high pressure on a diamond hydraulic press. The sintering conditions are 5GPa, 1400℃, and the sintering holding time is 50min. After slowly cooling to room temperature, three pieces of Φ14mm×2mm silicon nitride ceramic sheet sintered body materials are obtained after pressure relief. The hardness of the sintered body material is measured to be 25GPa, and the fracture toughness is 12.8MPa·m 1 / 2 .

[0031] Example 3

[0032] As attached Figure 1 As shown: Select α-Si with a particle size of 0.5-1μm and a mass of 5g 3 N 4 , Sintering aid ZrO 2 and binder W, Co, Cr mixed powder as the initial raw material (α-Si 3 N 4, the mass ratio of sintering aid and binder is 7:0.5:2.5 (W:Co:Cr=30:0.5:1). After being fully wet-mixed by vacuum high-energy ball milling for 5h, the mixed raw material is dried at 70℃ in a vacuum drying oven. The cylindrical green body is pre-pressed at a pressure of 15MPa using a four-column press, and the cylindrical green body is loaded into a vacuum tube furnace cavity. The green body is subjected to high-temperature treatment at 1550℃ for 30min under a vacuum environment. The carbon-free green body after high-temperature treatment is crushed, 0.07g of graphite powder is added, and after being fully mixed by vacuum low-speed ball milling for 3h, it is pre-pressed at 15MPa, and the carbon-containing raw material green body 1, small graphite flakes 2 and plugs 3 are loaded into the graphite tube 4. Three carbon-containing raw material green bodies 1 and four small graphite flakes 2 are arranged alternately in sequence. The inner diameter of the graphite tube 4 is 17mm and the height is 16mm. Then put the graphite cavity and components 5-7 into the pyrophyllite composite block 8. The size of the pyrophyllite composite block 8 is 32.5mm×32.5mm×32.5mm. The diameter of the synthetic cavity is 18mm. The silicon nitride is sintered at high temperature and high pressure on a diamond hydraulic press. The sintering conditions are 4.5GPa, 1250℃, and the sintering holding time is 30min. After slowly cooling to room temperature, three pieces of Φ14mm×2mm silicon nitride ceramic sheet sintered body materials are obtained after pressure relief. The hardness of the sintered body material is measured to be 20GPa, and the fracture toughness is 8.2MPa·m 1 / 2 .

[0033] The present invention uses α-Si 3 N 4 The micro powder is a hard phase matrix, with zirconium dioxide (ZrO 2 ) as a sintering aid to promote Si 3 N 4 The transformation from α phase to β phase increases the matrix density, and tungsten (W), cobalt (Co), chromium (Cr), nickel (Ni), titanium (Ti) and other elements are added as a binder phase for toughening. A small amount of graphite powder (C) is added, and high pressure sintering technology is used to adopt a closed sintering cavity to synthesize β-Si 3 N 4 The present invention uses high-energy ball milling to refine particles, melts metal infiltrates the green body under vacuum conditions, adds graphite powder and mixes it by low-speed ball milling, and produces β-Si with uniform texture, high strength, good toughness and wear resistance under high-pressure driving. 3 N 4 Sintered body, strong operability, and suitable for industrial large-scale production.

[0034] The above schematically describes the present invention and its implementation methods, which are not restrictive. The drawings show only one implementation method of the present invention, and the actual structure is not limited thereto. Therefore, if a person skilled in the art is inspired by it and does not deviate from the technical solution of the present invention, and designs a structure and implementation similar to the technical solution based on the above implementation examples without creativity according to the technical essence of the present invention, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a ceramic blade material for a tile cutter, characterized in that: The method comprises the following steps: ①. Select α-Si3N4 powder, sintering aid powder and binder powder as raw materials; ②, the mixed powder raw materials selected in ① above are mixed in a certain proportion, and after being fully wet-mixed by vacuum high-energy ball milling for 1-10 hours, they are dried in a vacuum drying oven to obtain a carbon-free mixed raw material; ③. Pre-press the carbon-free mixed raw material obtained in ②, load the cylindrical green body into a vacuum tube furnace cavity, and use vacuum sintering technology to perform high-temperature treatment on the green body in a vacuum environment; ④. Crush the carbon-free green body obtained after high-temperature treatment in ③, add a small amount of graphite powder, and fully mix by vacuum low-speed ball milling to obtain a carbon-containing mixed raw material, and pre-press and shape to obtain a carbon-containing green body; ⑤. Load the carbon-containing blank in ④ into a graphite heating cavity, assemble the pyrophyllite composite block, and sinter it under high temperature and high pressure using a diamond hydraulic press to complete the preparation of the β-Si3N4 sintered body.

2. The method for preparing a ceramic blade material for a tile cutter according to claim 1, characterized in that: In step ①, the raw materials are all nano-scale or micron-scale powder materials, with a single particle size or a mixture of multiple particle sizes. The sintering aid is ZrO2, the binder is W, Co, α-Si3N4, the mass ratio of the sintering aid and the binder is 7:X:3-X (X=0.05-0.5), and the mass ratio of the binder W and Co is 30:0.5-2.

3. The method for preparing a ceramic blade material for a tile cutter according to claim 1, characterized in that: The binder also includes other elements Cr or Ni or Ti or a mixture thereof, and the mass ratio of Co to other elements in the binder is 1:0-2.

4. The method for preparing a ceramic blade material for a tile cutter according to claim 1, characterized in that: In step ②, the high-energy ball mill has a rotation speed of 500-800 rad / min, a ball milling time of 1-10 h, and a vacuum drying oven drying temperature of 70°C.

5. The method for preparing a ceramic blade material for a tile cutter according to claim 1, characterized in that: In step ③, the powder molding pressure is 5-20 MPa, the high temperature treatment temperature is 1500-1700°C, and the treatment time is 10-30 min.

6. The method for preparing a ceramic blade material for a tile cutter according to claim 1, characterized in that: In step ④, the mass ratio of graphite powder to W powder is 1:16, the low-speed ball milling speed is 200-300 rad / min, the ball milling time is 1-5h, and the powder molding pressure is 5-20MPa.

7. The method for preparing a ceramic blade material for a tile cutter according to claim 1, characterized in that: In step ⑤, the carbon-containing body is loaded into a graphite tube, the graphite tube is placed in a pyrophyllite composite block cavity, and high-temperature and high-pressure sintering is performed on a diamond hydraulic press. The sintering conditions are 4.0-5.5 GPa, 1250-1600°C, and the sintering holding time is 15 min-1 h.

8. The silicon nitride ceramic prepared according to the method for preparing a ceramic blade head material for a tile cutter according to any one of claims 1 to 7 is used to manufacture a cutter tool for construction.

Citation Information

Patent Citations

  • Si3N4 / TiC / graphene composite ceramic cutter material with mechanical aeolotropy and preparation method thereof

    CN106145958A

  • Technology for using vibration pressure sintering method to prepare silicon nitride ceramics

    CN107954724A

  • Preparation method of high-thermal-conductivity silicon nitride substrate

    CN111170745A

  • Silicon nitride ceramic sintered body and preparation method thereof

    CN115180960A

  • Preparation method of silicon nitride / tungsten high-temperature co-fired ceramic substrate

    CN115536402A